Building profits in the construction industry - Kubal, Michael T. (McGraw Hill, 2000)
Provides a base of what is happening with the construction industry through changes in employment with downsizing, lack of adequate trained personnel, emphasis on improved quality, changing procurement methods, new realities of marketing and sales, the technological influence, and consistent drive toward bottom line results. Focuses on the how-to-in understanding current markets, how to maximize results, and how to best prepare for the 21st century.